2020
DOI: 10.1038/s41437-020-0328-6
|View full text |Cite
|
Sign up to set email alerts
|

Varietal variation and chromosome behaviour during meiosis in Solanum tuberosum

Abstract: Naturally occurring autopolyploid species, such as the autotetraploid potato Solanum tuberosum, face a variety of challenges during meiosis. These include proper pairing, recombination and correct segregation of multiple homologous chromosomes, which can form complex multivalent configurations at metaphase I, and in turn alter allelic segregation ratios through double reduction. Here, we present a reference map of meiotic stages in diploid and tetraploid S. tuberosum using fluorescence in situ hybridisation (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 82 publications
(118 reference statements)
4
21
0
Order By: Relevance
“…2 ). These results are in accordance with recent findings published by Choudhary et al ( 2020 ). These authors presented a map of meiotic stages in S. tuberosum in one diploid and three tetraploid varieties using fluorescence in situ hybridization (FISH).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…2 ). These results are in accordance with recent findings published by Choudhary et al ( 2020 ). These authors presented a map of meiotic stages in S. tuberosum in one diploid and three tetraploid varieties using fluorescence in situ hybridization (FISH).…”
Section: Discussionsupporting
confidence: 94%
“…They concluded that bivalent chromosome associations are the most common in metaphase I of tetraploid potatoes. Likewise, the broad range of multivalent signature rates observed in our study (2.2~39.2%) was also observed by Choudhary et al ( 2020 ) (7~48%). Similarly, as their observations differed depending on variety and chromosome, in our study, the variation occurred by parents and by linkage groups.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, most of the parental meiotic configurations based on the B2721 population were inferred as bivalents (62.3% on average) since they involved two homologs exchanging segments during the metaphase I (Figure 2). These results are in accordance with recent findings published by Choudhary et al . (2020).…”
Section: Discussionsupporting
confidence: 94%
“…They concluded that bivalent chromosome associations are the most common in metaphase I of tetraploid potatoes. Likewise, the broad range of multivalent signature rates observed in our study (2.2∼39.2%) was also observed by Choudhary et al . (2020) (7∼48%).…”
Section: Discussionsupporting
confidence: 92%
“…The convergent tasks detected (other meiotic pathway, chromosome arrangement or remodeling, ABA cues and ion transport) offer initially insights into the noticeable challenges related to polyploidization. Another example, investigating the meiosis of autotetraploid potato S. tuberosum revealed variety of challenges in correct segregation and recombination of multiple homologous chromosomes that constraints on meiotic chromosomal configuration [2].…”
Section: Introductionmentioning
confidence: 99%